2012
DOI: 10.4236/health.2012.42015
|View full text |Cite
|
Sign up to set email alerts
|

Patient dose from radiographic rejects/repeats in radiology centers of Urmia University of Medical Sciences, Iran

Abstract: Medical diagnostic X-rays are the largest manmade source of ionizing radiation received by the members of the general public. The aim of this study was to evaluate the radiographic reject/repeat rate and also to determine dose to the patients from radiographic rejects/repeats in radiology centers of Urmia University of Medical Sciences. During a 4 month period the most frequently examinations were chosen in three radiology centers. A form was designed as a reject/repeat analysis form for radiographers to compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 18 publications
1
16
0
2
Order By: Relevance
“…Although constituting 40-60% of all rejects in the analog systems, the relative contribution of exposure errors in the digital systems has been reduced to less than 15%. [12] In KAMC, the rejection due to artifact is 13%. Comparable studies show rejection due to artifact ranging from 7% up to 11% depending on the type of hospital.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although constituting 40-60% of all rejects in the analog systems, the relative contribution of exposure errors in the digital systems has been reduced to less than 15%. [12] In KAMC, the rejection due to artifact is 13%. Comparable studies show rejection due to artifact ranging from 7% up to 11% depending on the type of hospital.…”
Section: Discussionmentioning
confidence: 99%
“…[10,11] In terms of body parts, the most frequently rejected radiographs are extremities and chest, followed by spine, pelvis, head and neck, and abdomen. [9,12,13] This is expected due to the fact that extremities and chest are the most common body parts radiographed in imaging department. The purpose of this study was to evaluate the radiographs reject rate and to identify the causes of rejection.…”
Section: Introductionmentioning
confidence: 99%
“…20 The radiation dose received by the patient will increase in line with radiographs image retrieval. 11 The higher radiation dose will increase the severity of the radiation effect. 12 Previous study reported a significant increase in GCF volume after exposure to panoramic radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…2 Repetition of radiography increases the radiation dose received by the patient. 11 The higher the radiation dose, the effect of radiation will increase in terms of severity and frequency. 12 Radiation protection can minimize the effect of radiation exposure on patients and operators.…”
Section: Introductionmentioning
confidence: 99%
“…Ces facteurs ont été mis en cause dans plusieurs études antérieures (Jabbari, Zeinali, & Rahmatnezhad, 2012;Abubakar, et al, 2016;Sniureviciute & Adliene, 2005). Ils ont été mis en cause dans plus de la moitié des rejets.…”
Section: Les Causes Du Rebut Des Clichés Et éValuation De La Perte Fiunclassified